Wetting and adhesion properties of rhamnolipid and surfactin. (August 2018) - Zdziennicka, Anna; Jańczuk, Bronisław
Abstract: The measurements of the contact angle of the aqueous solution of rhamnolipid (RL) and surfactin (SF) on polytetrafluoroethylene (PTFE), polyethylene (PE), polymethyl methacrylate (PMMA), nylon 6 and quartz were performed. The obtained values of the contact angle were analyzed by applying the components and parameters of the surface tension of aqueous solution of surfactants, PTFE, PE, PMMA, nylon 6 and quartz. This analysis showed that the contact angle of the solution on the hydrophobic solids can be predicted theoretically knowing the Lifshitz-van der Waals component of the water surface tension, the surface tension of the solids and that of the solution. Based on the contact angle values the critical surface tension of studied solids wetting, the adsorption of surfactants at the solid-water interface, the standard Gibbs free energy of adsorption as well as the work of adhesion of solutions to PTFE, PE, PMMA, nylon 6 and quartz surfaces were determined. It proved that the critical surface tension of wetting of the studied solids is different from their surface tension and that the work of adhesion of the aqueous solutions of RL and SF to PTFE, PE, PMMA, nylon 6 and quartz surfaces can be predicted from the components and parameters as well as the total surface tension of solids and solutions.